The skin model, a comprehensive geometric model for engineering design - Anwer, Nabil; Ballu, Alex; Mathieu, Luc (CIRP annals, 2013)
The modelling of product shapes and dimensions is now largely supported by geometric modelling tools. However, the underlying geometrical variations cannot be addressed efficiently when covering the overall product life cycle. The fundamental concept of skin model has been developed as an alternative to the nominal model and covers geometric deviations that are expected, predicted or already observed in real manufacturing processes. This paper investigates the fundamentals of the skin model at a conceptual, geometric and computational level. Representation and simulation issues for product design are presented. Finally, applications and perspectives are highlighted.